Study of Knowledge, Attitude and Practices Towards HIV/AIDS and Sexually Transmitted Infection among MBBS Preclinical Students in UCMS, Nepal - Srivastava, Suman Lata (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Knowledge, attitude and behavior of a medical professional play an important role in the quality of care that an HIV/AIDS positive person receives and in shaping their attitude towards the disease. Thus, it is important that medical students, who would be treating such persons in near future, have the appropriate knowledge and attitudes. This study explores both these factors among pre-clinical medical students in Nepal. MATERIAL AND METHODS A cross sectional study was carried out among 200 ﬁrst and second year MBBS students at Universal College of Medical Sciences Teaching Hospital, Nepal. A pre-tested, structured questionnaire was used to evaluate respondents’ knowledge towards of HIV causes and transmission and their attitudes towards HIV/AIDS and people living with it. RESULTS Knowledge among respondents was high overall and showed an improvement from ﬁrst to second year. Some improvement areas regarding transmission from lactating mother to infant, transmission via sweat, kissing etc and infant’s BCG vaccination management were found. Respondent’s attitudes too were generally positive but with some signiﬁcant stigmatizing notions such as isolation and entry bans of HIV positive people. CONCLUSION Knowledge of pre-clinical MBBS students is generally high though there are some improvement areas in HIV transmission. The attitude too is positive overall with a small minority holding stigmatizing views. Progression from ﬁrst to second year has a positive impact on both knowledge and attitudes.